Econometric Analysis of Unemloymwent Rate and RGDP Trends Tradeoff Dynamics in Eastern European Countries - Oliskevych, Marianna; Bazhenova, Olena; Lukianenko, Iryna; Babenko, Vitalina; Beregova, Galyna (International Journal of Economics and Financial Issues, 2025)
The paper provides econometric analysis of unemployment rates (UR) and real GDP (RGDP) trends and their tradeoff dynamics for 11 Eastern EU countries (Poland, Croatia, Czech Republic, Romania, Slovakia, Slovenia, Hungary, Bulgaria, Estonia, Latvia, and Lithuania) from 1996 to 2024. The econometric modeling highlights a range of peculiarities that define their economic landscapes. This investigation reveals that all 11 countries share the common trait of an inverse UR–RGDP relationship, with downturns like 2008 and 2020 triggering UR spikes followed by recoveries tied to RGDP growth, reflecting a shared EU integration trajectory. The peculiarities underscore a spectrum of economic adaptability. Industrial powerhouses like Poland, Czech Republic, and Hungary demonstrate faster UR declines and robust RGDP growth, while tourism-dependent Croatia and tech-driven Estonia show distinct recovery trajectories, highlighting diverse economic adaptability with lagged or non-linear responses. The analysis suggests that diversification, as seen in Romania and Bulgaria with steady RGDP growth moderating UR volatility, enhances economic resilience, while volatile recoveries in Latvia and Lithuania indicate structural rigidities that warrant targeted policy interventions. The findings underscore the importance of diversification and sector-specific resilience in shaping labor market and economic outcomes across the region.